Effect of Core Strengthening and Posture Correction Exercises with Stretching on Sciatic Nerve Root Compression - Nishitha, .; Prathap, Suganthirababu; Vinodhkumar, Ramalingam; Vignesh, Srinivasan; Kumaresan, Abathsagayam; Jagatheesan, Alagesan (INTI International University, 2023)
Background: Sciatica is a common source of pain and discomfort that lasts longer and is more severe than lower back pain. Between 13 and 40% of people are thought to be affected by this condition at some point in their lives. It usually deteriorates because of bad posture. Sciatica has the potential to become chronic and intractable, with serious socioeconomic consequences. Objective: To ascertain the impact of core strengthening and posture correction exercises with stretching on sciatic nerve root compression. Methodology: Thirty-two sciatica patients were selected using inclusion and exclusion criteria. They were split into two groups randomly: conventional (n = 16) and experimental (n = 16). Core strengthening exercises along with TENS were given to the conventional group, whereas posture correction exercises with stretching along with TENS were given to the experimental group. All the interventions were performed 5 times a week for 6 weeks, with 2 sets of 10 reps. As an outcome measure, the Oswestry disability index was utilized to assess each subject's level of pain and disability. Results: The mean and SD value of core strengthening at the pre-test was 50.63 and 6.18 and for the post-test was 34.00 and 4.32. As for posture correction exercises with stretching, the mean and SD value of pre-test was 50.75±5.16 and the post-test was 21.88± 3.76, respectively. Conclusions: The study concludes that the posture correction with stretching activities was found to be more beneficial than core strengthening in reducing sciatic pain and disability.